DESCRIPTIVE ANALYSIS OF INFLATION, MONEY SUPPLY, DEPOSITS AND INTEREST RATE IN INDONESIA - Karnadi Karnadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Prof Dr Hazairin, SH, 2015)
In this study were analyzed descriptively inflation, money supply and the interest rate ondeposits in Indonesia. The data used is secondary data directly on the object of researchstudies and data already available on the website of Bank Indonesia and the Ministry ofFinance. Several previous studies have been conducted to look at the relationship andwant to know the condition of inflation, the money supply and interest rates on deposits inIndonesia. Supported by several theories about Inflation, Money Supply and Interest RateDeposit, this research can be done to look at the various influences of these variables.The method used is descriptive analysis. The purpose of this study was to determine thecondition of Inflation, Money Supply and Interest Rate Deposit in Indonesia. Theseresults indicate that the variables Inflation, Money Supply and Interest Rate Deposit inIndonesia. These results indicate that inflation and interest rates on deposits experiencedwhile money beredarar fluctuate from year to year increase.